Possible Role of Protein CPG15 in Hippocampal Mossy Fiber Sprouting Under Conditions of Pentylenetetrazole Kindling - Song, M.Y.; Tian, F.F.; Dang, J.; Huang, W.J.; Guo, J.L. (Нейрофизиология, 2015)
We examined changes in expression of the candidate plasticity-related gene 15 (CPG15) in
the dentate gyrus (DG) and hippocampal CA3 region in the pentylenetetrazole (PTZ) kindling
model and investigated the role of this gene in the phenomenon of mossy fiber sprouting
(MFS). Experimental rats were divided into the control and PTZ groups. The epileptic model
was created by intraperitoneal PTZ injection, while control rats were injected with saline.
At days 3, 7, 14, 28, and 42 after the first PTZ injection, Timm staining was scored in the
CA3 hippocampal area, and a product of CPG15 (protein CPG15) was labeled in the DG
stratum granulosum and in the CA3 area using immunohistochemistry. The Timm scores in
the CA3 region increased gradually from day 3 and were significantly higher than those in
the control within the subsequent period. The level of CPG15 protein in the DG and CA3
area decreased gradually until day 14 and returned to the normal level at day 28. The results
obtained indicate, for the first time, that CPG15 may be involved in the process of MFS.
Understanding the molecular mechanisms underlying this phenomenon may lead to successful
therapeutic interventions that limit epileptogenesis. Ми досліджували зміни експресії продукту гена CPG15
у зубчастій звивині (ЗЗ) та зоні CA3 гіпокампа в моделі
пентилентетразолового (ПТЗ-) кіндлінгу та можливу роль цього гена у феномені спрутингу моховитих волокон
(СМВ). Піддослідні щури були поділені на групи контролю та ПТЗ-кіндлінгу. Модель епілепсії створювали за допомогою внутрішньоочеревинних ін’єкцій пентилентетразолу
(ПТЗ); контрольним щурам ін’єкували фізіологічний
розчин. На третю, сьому, 14-ту, 28-му та 42-гу добу після
першої ін’єкції ПТЗ оцінювали забарвлення, за Тіммом, у
зоні CA3. Локалізацію протеїну CPG15 у stratum granulosum ЗЗ та зоні CA3 гіпокампа визначали з використанням
імуногістохімічної методики. Інтенсивність забарвлення, за
Тіммом, у зоні CA3 поступово збільшувалася починаючи з
третьої доби та була вірогідно вищою, ніж така в контролі,
протягом усього наступного періоду. Рівень протеїну CPG15
у ЗЗ та полі CA3 поступово зменшувався до 14-ї доби та
повертався до нормальних значень на 28-му добу. Отримані
результати вперше вказують на те, що CPG15 може бути
залученим у процес СМВ. Зрозуміння молекулярних механізмів, на яких базується цей феномен, може призвести до розробки успішних терапевтичних заходів, котрі обмежували б епілептогенез.